EFFECTS OF Bacillus sp PROBIOTICS ON GROWTH AND SURVIVAL OF Carassius auratus IN URBAN FISH FARMING - Syakir, Muhammad Sabiq; Mulyani, Yuniar; Rostika, Rita; Haetami, Kiki; Davinci, Leonardo; Karsih, Okta Rizal (Asian Journal of Aquatic Sciences, 2025)
This study aims to determine the optimum density of Bacillus sp. bacteria applied to feed to increase the growth of C. auratus maintained in a fish farming system in an 80 L bucket. As a form of urban farming, this research was conducted in the yard of Building 1 of the Faculty of Fisheries and Marine Sciences, UNPAD. This study used an experimental method with a Completely Randomized Design model consisting of 4 treatments and three replications, namely treatment A (control), treatment B (Bacillus sp 106 CFU/mL), treatment C (Bacillus sp. 108 CFU/mL), and treatment D (Bacillus sp 1010 CFU/mL). Observations were made for 60 days. Observation parameters were weight growth, length growth, specific growth rate, feed efficiency, survival, and water quality. The results of this study indicate that treatment C (Bacillus sp 108 CFU/mL) was the most effective in increasing the growth of C. auratus, as seen from the absolute weight growth of 61.20 g, absolute length growth of 1.30 cm, specific growth rate of 0.77%/day, feed efficiency of 38%, and fish survival rate of 96% which were significantly different compared to the others.